Prevalensi efek samping farmakoterapi terhadap penderita skizofrenia di Rumah Sakit Jiwa Bangli, Propinsi Bali - Subramaniam, Sharmadave; Sasmita, Ni Putu Suweni; Jaya Lesmana, Cokorda Bagus (E-Jurnal Medika Udayana; Vol 7 No 1 (2018): E-Jurnal Medika Udayana, 2018)
Schizophrenia is persisting mental illness and need a long-life medication, with psychotic symptoms and loss of specific cognitive functions. This study aims to identify the prevalence of side effects of pharmachotherapy on schizophrenia patients in RSJ Bangli. Forty-two sample was taken from medical record in Asylum of Bali based on the report when patient is admitted to emergency department. The data then extracted into extraction form that is previously made and analyzed with software SPSS 20. The youngest patient is 21 years old. Gender comparison of man 92.9% and woman 7.1%. Patients with unmarried status 59.5%, married patients 35.7% and divorced 4.8%. No widowed and unknown patient found from the data. The side effect of pharmachotherapy includes extrapyramidal syndrome with 14 patients (33.3%), tardive dyskinesia and other tardive syndromes with 18 patients (42.9%), dyslipidemia with 2 patients (4.8%) and insulin resistance and hyperglycemia with 8 patients (19%). In this study, it is found that among 42 patients that is taken randomly, more than 40% has tardive dyskinesia and other tardive syndromes. Other side effects of pharmachotherapy are also varied. Risk factor of older age, greater adiposity, ethnicity could further contribute to the worsen effects of pharmachotherapy in schizophrenia. Keywords: schizophrenia, side effects, pharmachotherapy